Early childhood experiences in language arts : emerging literacy - Machado, Jeanne M. (Delmar, 1999)
Language development-emerging literacy in the young child. Developing language arts programs. Listening-literate beginnings. Introducing literature. Speech growth-conversation, expression, and dramatization. Writing - print awareness and use. Reading-a language art. Settings promoting literacy-at home and school.